(untitled) (ex æquo, 2023)
The normative invisibility of psychosocial risks that affect working women. The Spanish case in a European perspective The present study intends to demonstrate how there is a double indirect discrimination in the normative system of prevention and social protection, studying for this purpose the Law of Prevention of Occupational Risks (LPRL) and the system of classification of occupational diseases regulated in the General Law of Social Security (LGSS). The main findings show how the LPRL does not develop the general security obligation in the face of psychosocial risks. In addition, once the risk has been overcome, the illnesses caused by psychological causes are not protected within the occupational diseases, being only possible to demonstrate their labor etiology indirectly through the so-called occupational diseases (art.156.2e, LGSS), which causes an underestimation of such pathologies that affect working women to a greater extent.